Clinical features of persistent postural-perceptual dizziness with isolated otolith dysfunction as revealed by VEMP and vHIT findings - Azami, Masato; Fushiki, Hiroaki; Tsunoda, Reiko; Kamo, Tomohiko; Ogihara, Hirofumi; Tanaka, Ryozo; Kato, Takumi (Frontiers in Neurology, 2023)
Background: Persistent postural-perceptual dizziness (PPPD) is a relatively new disease entity, with diagnostic criteria published by the Bárány Society. PPPD is often preceded by a peripheral or central vestibular disorder. It is not clear how coexisting deficits due to preceding vestibular disorders affect PPPD symptoms. Objective: This study aimed to characterize the clinical features of PPPD with or without isolated otolith dysfunction using vestibular function tests. Methods: The study included 43 patients (12 males and 31 females) who were diagnosed with PPPD and completed oculomotor-vestibular function tests. The Dizziness Handicap Inventory (DHI), Hospital Anxiety and Depression Scale (HADS), Niigata PPPD Questionnaire (NPQ), and Romberg test for stabilometry were examined. The 43 patients with PPPD were classified into four categories based on vestibular evoked myogenic potential (VEMP) and video head impulse test (vHIT) results: normal function for both semicircular canals and otoliths (normal), isolated otolith dysfunction (iOtoDys), isolated semicircular canal dysfunction (iCanalDys), and dysfunction of both otoliths and semicircular canals (OtoCanalDys). Results: Among the 43 patients with PPPD, the iOtoDys group was the largest (44.1%), followed by the normal group (37.2%), iCanalDys group (9.3%), and OtoCanalDys group (9.3%). Eight of the 19 iOtoDys patients showed both abnormal cVEMP and oVEMP responses unilaterally or bilaterally (both sacculus and utriculus damage type), whereas 11 showed either an abnormal cVEMP or an abnormal oVEMP response (either sacculus or utriculus damage type). In a three-group comparison of the both sacculus and utriculus damage type, the either sacculus or utriculus damage type, and the normal group, the mean total, functional, and emotional DHI scores were significantly higher for the both sacculus and utriculus damage type than for the either sacculus or utriculus damage type. The Romberg ratio, a measure of stabilometry, was significantly higher for the normal group than for the both sacculus and utriculus damage type and the sacculus or utriculus damage type in the iOtoDys group. Conclusions: The coexistence of sacculus and utriculus damage may exacerbate dizziness symptoms in patients with PPPD. Determining the presence and extent of otolith damage in PPPD may provide useful information on the pathophysiology and treatment strategies of PPPD.